Using Instagram Reels as a Media for Government Public Service Information - Sulistyo, Muhammad Fijar; Sukmajatnika, Dimas Zainuddin; Syaputra, Riczky (PERSPEKTIF, 2024)
Researchers use the theory of new media characteristics proposed by Denis McQuail to reveal the reasons for using Instagram Reels by the Directorate General of Immigration as the main media in the publication of Letters of Support for Work and Holiday Visa (SDUWHV) services. The approach used is qualitative with descriptive methods. This research uses two data sources, namely primary and secondary. Primary data was obtained by interviewing sources, while secondary data was collected by library research and observing the Directorate General of Immigration's Instagram Reels social media. The research results show that the reasons for using Instagram Reels as SDUWHV information media are in line with Denis Mcquail's theory of new media characteristics, namely interactivity, social presence, media richness, autonomy, elements of playfulness, and privacy. The practical significance of this research lies in its ability to show how government agencies can use social media to increase public engagement in their programs. In addition, this research also provides insight into how government agencies can innovate their communication strategies to adapt to changes in media consumption behavior, especially among the younger generation who are active users of social media. Thus, this research is not only relevant for public and government communication practitioners but also for academics who are interested in understanding the dynamics of communication in the digital era and how government institutions can utilize new media for publication and educational purposes.